General characteristics of medical education in Mexico. A look from medical schools - Germán E Fajardo-Dolci; Javier Santacruz-Varela; Eleazar Lara-Padilla; Eduardo García-Luna Martínez; Alejandro Zermeño-Guerra; Julio César Gómez (Instituto Nacional de Salud Pública, 2019)
Objective. To know the characteristics of medical education and identify its strengths and weaknesses. Materials and methods. A transversal and quantitative study of the characteristics of medical education in 29 medical schools in Mexico was carried out, between April and September 2017. Questionnaire with Likert scale was applied to explore context, regulation, structure, process, results and impact of medical education. Bivariate analysis was performed with a Chi square test and the significance level was equal to or less than 0.05. Results. The political context obtained 64%, economical context 10% and mechanisms of regulation 31%. The educational structure was 61% and the social impact was 93%. Conclusions. Public policies, regulatory mechanisms and public investment must be strengthened to improve the quality of medical education.